Zionist Israel and the Question of Palestine : Jewish Statehood and the History of the Middle East Conflict - Amar-Dahl, Tamar (2016)
Tamar Amar-Dahl offers a profound analysis of Israel’s political order and culture and the role of Zionism. The study uncovers the discrepancy between the Western democratic self-image of Israel and its military influenced practical approaches to civil society. It presents in-depth the historical developments, the political repercussions and the possible perspectives for a peaceful solution with the Arab neighbors.